2012
DOI: 10.1175/jcli-d-11-00189.1
|View full text |Cite
|
Sign up to set email alerts
|

The Initiation of Modern “Soft Snowball” and “Hard Snowball” Climates in CCSM3. Part I: The Influences of Solar Luminosity, CO2 Concentration, and the Sea Ice/Snow Albedo Parameterization

Abstract: The ''Snowball Earth'' hypothesis, proposed to explain the Neoproterozoic glacial episodes in the period 750-580 million years ago, suggested that the earth was globally covered by ice/snow during these events. This study addresses the problem of the forcings required for the earth to enter such a state of complete glaciation using the Community Climate System Model, version 3 (CCSM3). All of the simulations performed to address this issue employ the geography and topography of the present-day earth and are em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
86
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 91 publications
13
86
2
Order By: Relevance
“…Simulation with a comprehensive Earth atmospheric general circulation model (AGCM) coupled to a slab ocean, without dynamic ocean heat transport, revealed an "eyeball" climate state, with a round area of open ocean centered at the substellar point and complete ice coverage on the nightside, even for very high CO 2 concentrations (4). In the presence of sea ice, ocean heat transport is likely to be especially important, because it is known from studies of the Snowball Earth phenomenon in Earth-like conditions that ocean heat transport is very effective in holding back the advance of the sea-ice margin (12)(13)(14). The distribution of sea ice on tidally locked exoplanets is only an issue for M stars, because planets with sufficiently dense atmospheres orbiting hotter stars in orbits close enough to yield tidal locking are likely to be too hot to permit ice and may even be too hot to retain water.…”
mentioning
confidence: 99%
“…Simulation with a comprehensive Earth atmospheric general circulation model (AGCM) coupled to a slab ocean, without dynamic ocean heat transport, revealed an "eyeball" climate state, with a round area of open ocean centered at the substellar point and complete ice coverage on the nightside, even for very high CO 2 concentrations (4). In the presence of sea ice, ocean heat transport is likely to be especially important, because it is known from studies of the Snowball Earth phenomenon in Earth-like conditions that ocean heat transport is very effective in holding back the advance of the sea-ice margin (12)(13)(14). The distribution of sea ice on tidally locked exoplanets is only an issue for M stars, because planets with sufficiently dense atmospheres orbiting hotter stars in orbits close enough to yield tidal locking are likely to be too hot to permit ice and may even be too hot to retain water.…”
mentioning
confidence: 99%
“…However, in other models, it is found that a state with tropical open-water may be stable even if the sea ice edge reaches as low as 10 • latitude (Chandler and Sohl, 2000;Baum and Crowley, 2001;Pierrehumbert et al, 2011;Abbot et al, 2011;Yang et al, 2012a,b). One of the reasons for the absence of runaway glaciation in these models may be associated with the relatively low sea ice and/or snow albedo employed, which restricts the strength of the albedo feedback Yang et al, 2012a). For instance, the sea ice albedo in EBM/ice sheet models has been set to be as low as 0.45 (Hyde et al, 2000;Peltier et al, 2004Peltier et al, , 2007Peltier, 2010, 2011), and the snow albedo in CAM3 and CCSM3 is set to 0.66-0.78 Abbot et al, 2011;Yang et al, 2012a), both of which are smaller than observations, 0.47-0.52 for bare sea ice, 0.55-0.66 for sea glacier and 0.75-0.87 for snow (Perovich, 1996;Warren et al, 2002;Warren and Brandt, 2006).…”
mentioning
confidence: 99%
“…For instance, the sea ice albedo in EBM/ice sheet models has been set to be as low as 0.45 (Hyde et al, 2000;Peltier et al, 2004Peltier et al, , 2007Peltier, 2010, 2011), and the snow albedo in CAM3 and CCSM3 is set to 0.66-0.78 Abbot et al, 2011;Yang et al, 2012a), both of which are smaller than observations, 0.47-0.52 for bare sea ice, 0.55-0.66 for sea glacier and 0.75-0.87 for snow (Perovich, 1996;Warren et al, 2002;Warren and Brandt, 2006). As the sea ice and/or snow albedo increases, it will clearly be easier to enter a globally ice-covered state (Lewis et al, 2003;Pierrehumbert et al, 2011;Yang et al, 2012a).…”
mentioning
confidence: 99%
See 2 more Smart Citations